PCR applied to the detection of Ralstonia solanacerum in potato fields (INNOTEC, 2013)
Bacterial wilt, caused by Ralstonia solanacearum, is a permanent threat for crops and under favorable conditions its consequences are devastating. The incidence of the disease is variable in Uruguay; since the seventies there have been several hard to prevent and control episodes. R. solanaearum has been detected in all the productive areas. It is a challenge to maintain continuous production and fields free from the pathogen. Since no effective chemistry agents against R. solanacearum exist, the available pest control strategies are crop rotation, disinfection of tools and use of certificated pathogen-free seed potato. In this work the detection of R. solanacearum in soil was optimized using PCR to identify how long the pathogen persists. The strategy was applied to four potato fields with different backgrounds, showing that the pathogen is able to stay viable for more than 10 years. The advantages and limitations of this method on complex samples were determined. These results help potato producers improve pest control management of the crop.
Keywords: Bacterial wilt; Solanum tuberosum; persistence